Upper Airway Dimensions in North Indian Population: A Possible Guide to Appropriate Length of Laryngoscope Blade - Jha, Deepak K.; Thakur, Anil; Tripathi, Chandra B.; Jain, Mukul; Kumari, Rima; Chaturvedi, Monali; Arya, Arvind (Indian Journal of Neurotrauma, 2016)
Background The use of adequate size of blade may help minimize failures of endotracheal intubation (ETI) in non–operating room (OR) settings which are usually done by non–anesthesia health care professionals (NAHP). Prospective study was done to assess the appropriate length of the laryngoscope blade for North Indian population.Materials and Methods Upper incisor-to-vallecula (UI-V), lower incisor-to-vallecula (LI-V), and lower end of mandible to hyoid (M-H) distances were measured on routine computed tomography (CT) images of head and neck, done in the neuroradiology department in successive patients older than 11 years of age with normal airway structures.Results A total of 126 patients, which included 53 females and 73 males with an average age of 34.5 years (range 14–67 years), formed the study group. UI-V of males and females were 7.35 ± 0.54 and 6.99 ± 0.51 cm, respectively, and the difference was significant. LI-V of males and females were 7.05 ± 0.51 and 6.66 ± 0.50 cm, respectively, and the difference was significant. M-H in males and females were 3.42 ± 0.63 and 3.59 ± 0.52 cm, respectively, and the difference was not significant. Open mouth CT in 11 patients revealed an average increase of 1.66 and 0.45 cm in UI-V and LI-V (n = 11), respectively, and 0.59 cm decrease in M-H (n = 9) which were significant.Conclusion Upper airway dimensions of the population may be the used for selecting appropriate size of blade of laryngoscope for ETI in non-OR settings especially by NAHP.
Keywords: laryngoscope blade size; endotracheal intubation; upper airway dimension; laryngoscopy